Crisis Response Patterns in Indonesian Philanthropy: How Religious Obligation Creates Revenue Resilience During the Covid-19 Pandemic - Dedy Hermawan; Mohammad Ali Fikri; Endar Pituringsih (Universitas Hayam Wuruk Perbanas, 2025)
This study analyzes differential crisis response patterns between religious and non-religious philanthropic organizations in Indonesia during the COVID-19 pandemic. Employing a longitudinal quantitative approach with panel data from 10 philanthropic organizations registered with the Indonesian Philanthropy Association from 2015-2024, we calculated annual revenue growth rates yielding 90 observations (45 per group). Mann-Whitney U Test results showed no statistically significant difference in average growth rates (U = 992.500; p = 0.872; r = 0.017). However, critical findings emerged from descriptive and temporal analyses: religious organizations maintained positive growth during the pandemic peak (8.78% in 2020; 5.41% in 2021) while non-religious organizations experienced contraction (-4.01% in 2021). Religious organizations demonstrated substantially lower volatility (SD = 18.57%) compared to non-religious counterparts (SD = 69.51%), indicating superior revenue predictability. Post-pandemic inverse correlation patterns (2022-2024) revealed qualitatively distinct recovery trajectories. Integrating Resource Dependence Theory and Institutional Theory, we argue that normative-religious funding bases (ZISWAF: Zakat, Infaq, Sadaqah, Waqf) create unique revenue stabilization mechanisms through obligatory giving structures and religious institutional legitimacy. These findings challenge conventional assumptions about revenue diversification and stability, demonstrating that funding source concentration can enhance resilience when grounded in normative-religious obligations. The study contributes theoretical nuance to organizational resource dependence literature and provides practical implications for philanthropic sector resilience strategies in crisis contexts.